Interactive game-based method training for early childhood Quran literacy - Mawaddah, Fahmy Ulfah; Romdoni, Romdoni; Utami, Fitria Budi; Setianti, Dewi; Parmiyatun, Parmiyatun; Hamim, Thoat; Nugraha, Wahyu Fajar; Setiani, Nurul (Universitas Muhammadiyah Magelang, 2025)
The significant difficulty faced by early childhood children in learning the hijaiyah letters due to monotonous and unengaging teaching methods poses a considerable challenge for Quran teachers and mosque activists in creating a more stimulating learning environment. This community service activity aims to train Quran teachers and mosque activists on innovative game-based methods for teaching Quran literacy to early childhood children. The training methodology includes lectures and interactive discussions. Lectures emphasize the importance of early Quran literacy and introduce game-based teaching techniques, including the use of hijaiyah cards, Islamic songs, and tactile media. Interactive discussions explore participants' experiences and provide solutions to the challenges of teaching the Quran. Evaluation results indicate that 85% of participants experienced an increased understanding of innovative Quran teaching methods. These findings suggest that an innovative game-based approach is effective in increasing children's interest in learning the Quran and facilitating their understanding of the hijaiyah letters. This program contributes to improving the quality of Quran learning for early childhood children within the mosque environment.